ANALISIS PRODUKSI PROGRAM PEMBERITAAN WAJAH SUMUT DI METRO TV BIRO MEDAN - Naftalia Simanjuntak; Besti Rohana Simbolon (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2019)
Television is a mass media that is currently widely used by the public to meet their information needs. Therefore, in order to meet the needs of the community, television stations provide news programs that provide information about various events in the lives of people. Metro TV does not only broadcast national and international news but is obliged to broadcast local news. Therefore in this study the writer wants to know how Metro TV Medan Bureau broadcasts its local news. This research method used is descriptive qualitative paradigm; the author only explains the process of producing news on the program North Sumatra Face in Metro TV Medan Bureau. The research informants are staffs who carry out the production of the North Sumatra Face program news. The results of the study explained that the North Sumatra Faces program was carried out in stages about the manuscript coverage from contributors to a news script spruced up in the news room, then it would be submitted to the editor for editing news images according to the script. The editor censors news images related to the elements of violence, pornography, blood, corpses, narcotics, and things that are prohibited in the KPI Act (Indonesian Broadcasting Commission) while the inhibiting factors are technical problems in the camera and computer that are in the studio and conducive field conditions.